2013
DOI: 10.4238/2013.january.24.9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between TYK2 and STAT3 genes and Crohn’s disease in the Malaysian population

Abstract: ABSTRACT. This study aimed to investigate the potential association of TYK2 and STAT3 genes with the susceptibility to Crohn's disease (CD) among Malaysians. DNA samples were obtained from 80 CD patients and 100 healthy controls. Polymerase chain reaction-restriction fragment length polymorphism methods were employed for genotyping, followed by statistical analysis. In our current study, none of the single nucleotide polymorphisms of either TYK2 or STAT3 was statistically associated with the susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…By analogy, it was also observed for IL-22 and STAT3 that in addition to the protective IECrestricted function in colitis, pathogenic effects may occur through perturbation of cytokine levels and/or immune cell recruitment/activation (62,63). The complex Tyk2 functions in mice are also reflected in humans, because variation occurs between human populations with respect to Crohn's disease susceptibility and its correlation to the Tyk2 and STAT3 loci (64). In conclusion, a future use of Tyk2 inhibitors (65,66) for the treatment of colitis should carefully consider whether the primary therapeutic benefit is expected through the regeneration of the epithelial barrier or the dampening of the hyperinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy, it was also observed for IL-22 and STAT3 that in addition to the protective IECrestricted function in colitis, pathogenic effects may occur through perturbation of cytokine levels and/or immune cell recruitment/activation (62,63). The complex Tyk2 functions in mice are also reflected in humans, because variation occurs between human populations with respect to Crohn's disease susceptibility and its correlation to the Tyk2 and STAT3 loci (64). In conclusion, a future use of Tyk2 inhibitors (65,66) for the treatment of colitis should carefully consider whether the primary therapeutic benefit is expected through the regeneration of the epithelial barrier or the dampening of the hyperinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] Several genes have been studied in a Malaysian cohort to explore their relationship with CD. [38][39][40][41] In this study, we aimed to investigate the association between the four target single nucleotide polymorphisms (SNPs), rs3807306, rs4728142, rs10954213 and rs11770589, in the IRF5 gene and the development of CD in the Malaysian population. The selection of these candidate SNPs were based on their significances in previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…The study of a Chinese Han population found the reverse, with no association identified with CD but an association with UC (38,39). In a Malay population, the (G) allele and (GG) genotype were identified to be protective against CD (40). The studies of rs2293152 in close populations have obtained very different results.…”
Section: Discussionmentioning
confidence: 85%